A Comparative Study of the Optimum Health and Health-Related Physical Fitness Level of State Level Players Boys and Girls at MBSPSU, Patiala - Himanshu Jogi; Sneh Lata (Recent Trends in Sports, 2026)
The study’s goal was to compare state-level player girls’ and boys’ optimal health and health-related physical fitness. Thirty individuals, including male and female state-level players from the Patiala district of Punjab, India, were chosen via purposeful random sampling. There were two distinct groups formed: There were fifteen participants in each group (15 females and 15 boys), with Group 1 being made up of girls and Group 2 being made up of boys. The variables of Optimum Health and Health-Related Physical Fitness were used to compare the two independent groups. A standardized Optimum Health Scale questionnaire was used to measure optimal health, and the AAHPER test was used to measure health-related physical fitness. The statistical technique used was the independent t-test with a confidence level of 0.95. The results showed that there was no discernible difference in Optimum Health between boys and girls at the state level, indicating that both groups retain a comparable degree of social, emotional, and mental well-being. Health-related physical fitness, on the other hand, showed a notable variation that may be explained by physiological variations, training intensity, and demands unique to a certain sport. Male athletes frequently exhibit greater levels of muscular strength and aerobic ability, but female athletes may excel in flexibility and balance, according to earlier studies. Fitness results can also be influenced by elements including diet, the caliber of coaching, and training facility accessibility.
Keywords: Sports Performance; comparative study; gender comparison; health-related physical fitness; optimum health; state-level players